Condors, Caracaras and the Antisana Ecological Reserve: Have Recent Conservation Efforts Backfired! - Mark R. Welford (Пернатые хищники и их охрана, 2018)
The 1993 creation of the 120,000 ha Antisana Ecological Reserve (Ecuador) to protect the unique flora and fauna surrounding the Volcano Antisana continues to evolve. In 1998, the La Mica dam was built to increase the capacity of Laguna La Mica and provide water for the Mica–Quito Sur Project. The Mica–Quito Sur Project is the result of an agreement between the Ecuadorian government, a conservation NGO, and a water and sewerage company (EMAAP-Q) to protect a watershed, its fauna and flora, and provide freshwater for Quito Sur. However, recently population decreases have been observed and tabulated by eBird among Condor (Vultur gryphus) and Caracara (Caracara plancus). The removal of cattle and sheep from the recently acquired Hacienda Antisana 4400 ha lot by EMAAP-Q in 2010 and intensified efforts at fire-suppression across the Reserve appears to have triggered these population declines. Cattle and sheep dung and their carcasses once contributed significant nutrients to the landscape while the diversity and number of paramo fire-successional patches supported higher biodiversity. Initial data acquisition suggests condor and caracara observations are declining, though these could be due to these raptors searching for food beyond the reserve. In fact, condor breeding numbers in Antisana have remained stable.